Narrativas infantis: avaliação das representações mentais e dos modelos internos de funcionamento em crianças vítimas e não vítimas de maus-tratos - Alvares, Joana (Universidade do Vale do Rio dos Sinos, 2016)
This study aimed to compare mental representations, internal working models in child victims and non-victims of ill-treatment, considering the representations of attachment and self in each group, as well as presenting the MSSB instrument as access resource to internal representations of children, analyzing their initial psychometric properties. With the internalization of early experiences and the link between child-caregiver, internal working models develop. These models can be understood as mental representation ability, which covers children's perceptions of the environment, themselves and others. Sample of ninety (90) children six (6) to ten (10) years (M=8.0, DP=1.8), 30 (thirty) accepted institutionally and victims of abuse and sixty (60) not victims. The instruments used were the SDQ and MSSB. Descriptive statistics, Mann-Whitney test and ANOVA for comparison between groups were employed. Regarding the contents of the SDQ, the maltreated children had borderline ratings (n=14, 46.7%) and abnormal (n = 16, 53.3%), while non-maltreated were classified as normal (n=60, 100%). Mental representations of maltreated children showed perceptions and more negative slant narratives when compared to non-abused. Indicating that child victims of abuse are more likely to develop more negative internal working models than non-victims, as well as representations of attachment less sensitive to your needs (M=0.62, SD=1.16) and representations themselves negative or grandiose (M=0.29, SD=1.29). Please note that further studies are developed, as well as preventive actions to better assessment of such cases, in addition to presenting the MSSB as a useful resource and tool for clinical and scientific work.
Keywords: Maus-tratos; Narrativas infantis; Representação mental; Modelos internos de funcionamento; Vínculo; Self; Maltreatment; Children's stories; Mental representation; Internal working models; Bonding; ACCNPQ::Ciências Humanas::Psicologia